Skeeter’s Ambition in Kathryn Stockett’s The Help - Amiluddin, Marsyagita; Litaay, Adeline Grace M (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study discusses Skeeter's ambition in Kathryn Stockett's The Help. The purpose of this study is to describe Skeeter's ambition, its causes, and its effects. In analyzing Skeeter’s ambition, the writer used the psychological approach and the theory of ambition by Judge and Kammeyer & Mueller. This study employed qualitative research. The findings reveal that Skeeter aspires to become a great writer. Skeeter's ambition is driven by two factors: internal and external. The internal causes of Skeeter's ambition are her deep love and passion for writing, her desire to uncover the truth, and her drive to fight for justice. The external causes of Skeeter's ambition are her wish to change her mother's traditional thought about women, her closeness to her nanny who is an African-American maid, and the social factors in her environment that frequently discriminate against black people. The effects of Skeeter's ambition are also twofold: positive and negative. The positive effects of her ambition are that Skeeter eventually gets a job in New York, and white women become aware of the unfair treatment experienced by African-American maids. The negative effects of her ambition are that Skeeter starts to be shunned by her friends and even ostracized by other white people. She is abandoned by her boyfriend, and African-American maids are fired by white families.